EFFECTIVE MANAGEMENT OF INSTITUTIONAL TRANSFORMATION IN VOCATIONAL EDUCATION: AN INTEGRATIVE MODEL FOR SAUDI ARABIA AND UZBEKISTAN - Abdulmajeed Nabeel Azouz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The paper examines the processes and challenges of institutional transformation in vocational education systems within different socio-economic and cultural contexts. It focuses on the comparative analysis of Saudi Arabia and Uzbekistan, identifying key factors such as governance models, labor market alignment, digital transformation, and stakeholder engagement. The study highlights the importance of integrating global best practices with national specificities to ensure the effectiveness and sustainability of reforms. Based on the findings, an integrative model is proposed to improve the management of institutional transformation in vocational education, emphasizing systemic coordination, adaptability, and context-sensitive policy implementation.